Focused attention predicts visual working memory performance in 13-month-old infants: A pupillometric study. (April 2019) - Cheng, Chen; Kaldy, Zsuzsa; Blaser, Erik
Highlights: We measured focused attention via task-evoked pupil dilation during a visual working memory task in 13-month-old infants. Pupil dilation during encoding significantly correlated with subsequent memory performance. This relationship between focused attention and memory was present both on the individual and the trial-by-trial level. Pupillometry is a promising new tool to measure focused attention with a high temporal resolution in infants. Abstract: Attention turns looking, into seeing. Yet, little developmental research has examined the interface of attention and visual working memory (VWM), where what is seen is maintained for use in ongoing visual tasks. Using the task-evoked pupil response – a sensitive, real-time, involuntary measure of focused attention that has been shown to correlate with VWM performance in adults and older children – we examined the relationship between focused attention and VWM in 13-month-olds. We used a Delayed Match Retrieval paradigm, to test infants' VWM for object-location bindings – what went where – while recording anticipatory gaze responses and pupil dilation. We found that infants with greater focused attention during memory encoding showed significantly better memory performance. As well, trials that ended in a correct response had significantly greater pupil response during memory encoding than incorrect trials. Taken together, this shows that pupillometry can be used as a measure of focused attention in infants, and a means to identify those individuals, or moments, where cognitive effort is maximized.